Psychological Well-Being Among Prospective Counselors at Semarang State University: The Roles of Self-Compassion and Coping Strategies - Anisa Khoiriyani; Kusnarto Kurniawan (STAI Auliaurrasyidin Tembilahan, 2026)
Psychological well-being is essential for prospective counselors because academic demands, social adjustment, and professional preparation may influence their mental health and readiness for future practice. Previous studies have generally examined self-compassion and coping strategies as independent predictors of psychological well-being, providing limited evidence regarding their combined contribution. This study aimed to examine the relationships between self-compassion, coping strategies, and psychological well-being among prospective counselors. A quantitative correlational design was employed involving 159 undergraduate students from the Guidance and Counseling Study Program at Semarang State University, selected using proportionate stratified random sampling. Data were collected using the Self-Compassion Scale, a Coping Strategies Scale, and the Psychological Well-Being Short Scale and analyzed through multiple linear regression. The results revealed significant positive relationships between self-compassion, coping strategies, and psychological well-being, both individually and simultaneously (p < 0.001). Together, self-compassion and coping strategies explained 52% of the variance in psychological well-being. These findings indicate that both variables play complementary roles in supporting prospective counselors’ psychological well-being. The study contributes empirical evidence for developing guidance and counseling services and self-development programs that strengthen self-compassion and adaptive coping strategies to enhance psychological resilience and professional readiness.